Comparison of different dosages of PCM incorporated wallpanels. Issue 1 (June 2020) - Lakshan, R R; Rosini, A M; Sathiyan, K; Sathyan, Dhanya; Mini, K M; Gangadharan, D
Abstract: In the modern world of development and technology, sustainable development is of greater need. One of the main factors that cause global warming is due to the usage of the artificial air conditioner in buildings. This study is the development of an eco-friendly wall panel for buildings which can reduce the usage of artificial air conditioner and to improve the thermal comfort in buildings in a sustainable way. To achieve this, PCM materials is used in mortar wall panels to regulate the temperature. PCM absorbs heat at higher temperature and releases the absorbed heat at lower temperature. In this study PCM were encapsulated to prevent them from being affected by the chemical environment. The encapsulated PCM were incorporated in mortar cubes and were made into wall panels. The PCM incorporated specimens were tested for compressive strength and thermal conductivity to study the hardened property and the heat transfer. The obtained results were compared with the control specimen to conclude the effect of PCM in mortar wall panels. The PCM incorporated specimens showed improved results compared to the control specimen.